Falling back : incarceration and transitions to adulthood among urban youth - Fader, Jamie J. (New Brunswick, N.J. : Rutgers University Press, 2013)
"Jamie J. Fader documents the transition to adulthood for a particularly vulnerable population: young inner-city men of color who have, by the age of eighteen, already been imprisoned. How, she asks, do such precariously situated youth become adult men? What are the sources of change in their lives? Falling Back is based on over three years of ethnographic research with black and Latino males on the cusp of adulthood and incarcerated at a rural reform school designed to address 'criminal thinking errors' among juvenile drug offenders. Fader observed these young men as they transitioned back to their urban Philadelphia neighborhoods, resuming their daily lives and struggling to adopt adult masculine roles. This in-depth ethnographic approach allowed her to portray the complexities of human decision-making as these men strove to 'fall back,' or avoid reoffending, and become productive adults. Her work makes a unique contribution to sociological understandings of the transitions to adulthood, urban social inequality, prisoner reentry, and desistance from offending." -- Publisher's website.
No love for the brothers : youth incarceration and reentry in Philadelphia -- Because that is the way you are : predictions of failure and cultural assaults inside Mountain Ridge Academy -- You can take me outta the hood, but you can't take the hood outta me : the experience of "reform" at Mountain Ridge Academy -- Nothing's changed but me : reintegration plans meet the inner city -- I'm not a momma's boy, I'm my own boy : employment, hustling, and masculinity -- I just wanna see a part of me that's never been bad : family, fatherhood, and furthe offending -- I'm finally becoming the person I always wanted to be : masculine identity, social support, and going straight -- I got some unfinished business : fictions of success at Mountain Ridge Academy's graduation ceremony.
Includes bibliographical references and index.
Keywords: Juvenile delinquents -- Pennsylvania -- Philadelphia; Juvenile delinquents -- Rehabilitation -- Pennsylvania -- Philadelphia; Juvenile corrections -- Pennsylvania -- Philadelphia; Juvenile justice, Administration of -- Pennsylvania -- Philadelphia; Mountain Ridge Academy